Rancang Bangun Sistem Informasi Surat di Majelis Pendidikan Dasar Dan Menengah Pimpinan Wilayah Muhammadiyah Daerah Istimewa Yogyakarta Menggunakan Metode Extreme Programming - jumadil abdul rahman (UIN Sunan Kalijaga Yogyakarta, 2018)
Correspondence is one activity that can not be separated from an organization, because the mail is one of the important communication media in the organization and communication with other organizations.High-intensity correspondence activities need to have a good management, so that the information conveyed can be delivered properly and safely. This management can also make letters well documented.System development in this research using Extreme Programming method. This method was chosen because the development is still done on a small scale. In addition, this method has a simple process, fast and precise because prioritizing the communication aspects between clients with developers. The built-in information system has features for receiving incoming mail, sending outgoing mail, sending and receiving mail dispositions, and sending and receiving memos. With this system can be effecient mail management and make it easy to manage the data letter itself. Keywords : Agile Process, Letter, Extreme Programming, PHP, Information System